Anomalous Long-Ranged Influence of an Inclusion in Momentum-Conserving Active Fluids - Thibaut Arnoulx de Pirey; Yariv Kafri; Sriram Ramaswamy (Physical Review X)
We show that an inclusion placed inside a dilute Stokesian suspension of microswimmers induces power-law number-density modulations and flows. These take a different form depending on whether the inclusion is held fixed by an external force—for example, an optical tweezer—or if it is free. When the inclusion is held in place, the far-field fluid flow is a Stokeslet, while the microswimmer density decays as 1/r^{2+ε}, with r the distance from the inclusion and ε an anomalous exponent which depends on the symmetry of the inclusion and varies continuously as a function of a dimensionless number characterizing the relative amplitudes of the convective and diffusive effects. The angular dependence takes a nontrivial form which depends on the same dimensionless number. When the inclusion is free to move, the far-field fluid flow is a stresslet, and the microswimmer density decays as 1/r^{2} with a simple angular dependence. These long-range modulations mediate long-range interactions between inclusions that we characterize.